Sustainability, productivity, profitability and nutritional diversity of six cropping systems under conservation agriculture: A long term study in eastern India - Dutta, Swaraj Kumar; Laing, Alison M.; Kumar, Sanjay; Shambhavi, Shweta; Kumar, Sunil; Kumar, Birender; Verma, Dharmendra Kumar; Kumar, Arun; Singh, Ravi Gopal; Gathala, Mahesh Kumar (Elsevier, 2023)
CONTEXT: Intensive cropping and elevated input use to achieve high crop yields have resulted in the injudicious use of resources and a consequent reduction in profit margins for farmers in the Eastern Gangetic Plains (EGP) region of South Asia. In this region rice-wheat (RW) under conventional tillage (CT) management is the most widely cultivated cropping system. While conservation agriculture (CA)-based management practices have been demonstrated to improve cropping system performance, they are considered by many farmers to be risky, and adoption of CA in rice-based cropping systems is low. There has been little agronomic research into alternative cropping systems to develop diversification options appropriate for the EGP. OBJECTIVE: We hypothesized that shifting from a conventional RW system to crop establishment practices which incorporate CA principles, combined with alternative crops could improve the whole cropping system in terms of productivity, profitability, and nutritional security (as crop protein). METHODS: A long-term experiment evaluated the performance of five maize-based cropping systems under CA-based management relative to CT RW. RESULTS AND CONCLUSIONS: CA-based practices improved the maize equivalent yield (MEY) by 4–15%, protein yield by 21%, input water productivity by 14–29% and the sustainable yield index by 10–11%, relative to the CT RW baseline. Cropping system labour requirements under CT were 12% higher than those under CA. The average cost of production under CT (USD $933) was 13–14% higher than in systems under CA; cropping systems under CA achieved net returns which were 31–34% higher. Diversifying from the traditional RW system to maize-based systems improved performance in all systems except maize-mustard. SIGNIFICANCE: These results demonstrate that while cropping system performance can be improved by applying CA-based management in RW systems, diversifying to maize-based systems in combination with CA may sustainably improve smallholder productivity and profitability while reducing some of the constraints to introducing CA in rice-based systems. These findings are important for the millions of smallholder farmers across the EGP to sustainably improve food and nutrition security for South Asia.